2013
DOI: 10.1159/000353898
|View full text |Cite
|
Sign up to set email alerts
|

Low Birthweight and Premature Birth Are Risk Factors for Podocytopenia and Focal Segmental Glomerulosclerosis

Abstract: Background: Recent reports suggest that low birthweight (LBW) is a risk factor for kidney diseases, including focal segmental glomerulosclerosis (FSGS), although the underlying pathological mechanism remains unknown. Podocyte loss triggers glomerulosclerosis; however, whether FSGS in LBW children is associated with podocytopenia is unclear. Methods: We reviewed the birthweights and gestational age of all patients who underwent renal biopsies from 1995 to 2011 at our Institute. Sixteen patients had FSGS, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…Their renal pathological findings included glomerulomegaly, hypertrophy of the juxtaglomerular apparatus, and perihilar segmental sclerosis, all consistent with glomerular hypertension [8][9][10]. Lesions of secondary segmental sclerosis caused by hyperfiltration tend to be in the perihilar area [8,10].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Their renal pathological findings included glomerulomegaly, hypertrophy of the juxtaglomerular apparatus, and perihilar segmental sclerosis, all consistent with glomerular hypertension [8][9][10]. Lesions of secondary segmental sclerosis caused by hyperfiltration tend to be in the perihilar area [8,10].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the presence of IUGR complicating prematurity increases the risk of CKD owing to impaired glomerulogenesis and podocyte injury [6,7]. A study of six patients with focal segmental glomerulosclerosis with a mean gestational age of 25.8 weeks and weight appropriate for age suggested that glomerular structure prematurity may be a more important factor than podocyte injury during the fetal period [9]. Nephrogenesis in humans begins during the 9th week of gestation, continuing up to week 36, with marked development occurring during the third trimester [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, numerous animal experiments and epidemiological studies have demonstrated a similar concept, additionally focused on the association between LBW and a low nephron number. 22,23 In addition, Hodgin et al 24 described the onset of secondary focal segmental glomerulosclerosis (FSGS) as being associated with proteinuria in six adults with a history of extreme prematurity, and Ikezumi et al 25 reported the number of podocytes per glomerulus in LBW-FSGS patients is lower than that seen in MCNS patients born with a normal birth weight. These findings support the hypotheses of both Barker and Brenner that LBW is associated with a reduced nephron number and therefore an increased risk of HTN/CVD and CKD in later life.…”
Section: Determining Factors Of the Nephron Numbermentioning
confidence: 99%
“…It is the leading cause of steroid-resistant nephrotic syndrome and the most common cause of chronic kidney disease among glomerular diseases (Reidy and Kaskel, 2007;D'Agati et al, 2011). The recent epidemiological data, suggesting that IUGR is a risk factor for glomerulosclerosis, was supported by the finding of higher Toxicology and Applied Pharmacology 287 (2015) [128][129][130][131][132][133][134][135][136][137][138] incidence of glomerulosclerosis among the patients who had low birth weight (Hodgin et al, 2009;Ikezumi et al, 2013). Animal studies also demonstrated that some suboptimal intrauterine environments, such as 50% intrauterine food restriction (Regina et al, 2001), could lead to glomerulosclerosis of adult IUGR offspring.…”
Section: Introductionmentioning
confidence: 99%